Breeding of a cordycepin-resistant and adenosine kinase-deficient sake yeast strain that accumulates high levels of S-adenosylmethionine. Issue 8 (3rd August 2019) - Kanai, Muneyoshi; Yasuda, Norito; Morimoto, Tomoko; Yoshida, Satoko; Nishibori, Nahoko; Mizunuma, Masaki; Fujii, Tsutomu; Iefuji, Haruyuki
ABSTRACT: Adenosine kinase ( ADO1 )-deficient mutants can be obtained from cordycepin-resistant strains, and the disruption of ADO1 causes S -adenosylmethionine (SAM) accumulation. To breed a high-SAM-accumulating yeast strain without genetic manipulation for industrial purposes, we bred a cordycepin-resistant strain using sake yeast kyokai No. 9 as the parent strain with a mutation in adenosine kinase ( ADO1 ) and acquired high-SAM-accumulating strain. In the bred strain (NY9-10), a single mutation (T258I) was present in the ADO1, and this mutation site is an ATP binding site and is highly conserved during evolution. Moreover, it was suggested that high accumulation of SAM and cordycepin resistance in NY9-10 was due to functional deficiency of ADO1 by this mutation. This strain is not a genetically-modified organism and can be employed for use in the food and medicine industry such as mass production and sake making. Graphical abstract: : We bred a cordycepin-resistant strain using sake yeast with a mutation in the ADO1 gene and obtained high-SAM-accumulating strains.